THE IMPACT OF PLEASE STRATEGY ON DEVELOPING PARAGRAPH WRITING SKILLS - Al-zu'bi, Mohammad; AL Kayed, Murad (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
This study aimed at investigating the effect of PLEASE (Pick, List, Evaluate, Activate, Supply, and End) strategy on developing paragraph writing skills of first-year students at Al-Balqa Applied University. It attempted to investigate the effect of PLEASE on paragraph writing achievement, compared to conventional method. Eighty-one EFL learners participated in the study at Ajloun College and were distributed on experimental and control groups. To fulfil the purpose of the study, the researchers applied pre- and post-test on both groups. After analysing the obtained data, the results indicated that PLEASE strategy affected paragraph writing positively. The study suggested several implications and recommendations for the future research.